Case report: Surgical closure of a facial defect in an African wild dog (Lycaon pictus) utilizing a transpositional skin flap - Brus, Armen M.; Spinner, Maureen; Rooney, Tess; Thompson, Kimberly A. (Frontiers in Veterinary Science, 2025)
Veterinary intervention in zoological species can be complicated by species-specific social dynamics. African wild dogs are a pack species and removal or separation of an individual may disrupt established pack hierarchy resulting in conspecific aggression. Therefore, medical interventions that optimize a quick return to health are ideal to minimize the duration of absence from the pack. These principles were utilized for a three-year-old male intact zoo-housed African wild dog (AWD) that presented with an episode of severe, acute, right-sided facial swelling. Swelling initially responded to medical management, however 6 days later the facial swelling worsened. The AWD was anesthetized and required extensive debridement of necrotic tissue. The absence of deep bacteria on histopathologic evaluation and a negative bacterial culture was suggestive of envenomation. The resultant open wound was managed every other day with debridement and topical manuka honey covered with a tie-over bandage. Each wound therapy treatment required general anesthesia but resulted in a healthy granulation tissue bed 9 days following initial debridement. Rather than proceeding with second intention healing and continued bandage changes, a transpositional skin flap surgical procedure was performed and enabled full closure of the large skin defect with complete tissue apposition and a good cosmetic outcome. The surgery reduced the number of anesthetic events and time that would have been required for second intention healing of the defect, which enabled a more rapid and ultimately successful reintegration of this individual into the pack without any perceived changes to the hierarchical structure.